Is the cryptocurrency market efficient? Evidence from an analysis of fundamental factors for Bitcoin and Ethereum - Blanka Łęt; Konrad Sobański; Wojciech Świder; Katarzyna Włosik (International Journal of Management and Economics, 2022)
This article sheds new light on the informational efficiency of the cryptocurrency market by analyzing investment strategies based on structural factors related to on-chain data. The study aims to verify whether investors in the cryptocurrency market can outperform passive investment strategies by applying active strategies based on selected fundamental factors. The research uses daily data from 2015 to 2022 for the two major cryptocurrencies: Bitcoin (BTC) and Ethereum (ETH). The study applies statistical tests for differences. The findings indicate informational inefficiency of the BTC and ETH markets. They seem consistent over time and are confirmed during the COVID-19 pandemic. The research shows that the net unrealized profit/loss and percent of addresses in profit indicators are useful in designing active investment strategies in the cryptocurrency market. The factor-based strategies perform consistently better in terms of mean/median returns and Sharpe ratio than the passive "buy-and-hold" strategy. Moreover, the rate of success is close to 100%.
Keywords: F31; G11; G15; 650; active strategies; cryptocurrency; fundamental factors; informational efficiency; Ledoit and Wolf test